THE EFFECT OF THE DC-SPUTTERING PROCESS ON CHANGES IN THE HARDNESS VALUE AND ELEMENTS COMPOSITION OF BIOCOMPATIBLE STAINLESS STEEL 316L MATERIAL - Sahabudin, Nuha Nazilah; Mukaromah, Uli Aprilia; Andriyanti, Wiwien; Sutanto, Heri (Website, 2023)
Titanium Dioxide (TiO2) thin films have intriguing optical, photocatalytic, and electrical properties and have been investigated for various applications, including solar cells, biomaterials, corrosion-resistant materials, and gas sensor. In this study, TiO2 thin films were deposited on the surface of 316L Stainless Steel to improve its mechanical properties as an implant material. The deposition method used was DC sputtering with variations in deposition times of 30, 60, 90, 120, and 150 minutes. Vickers hardness test and SEM-EDX characterization were carried out to determine the hardness value, elemental composition, and thickness of the TiO2 thin film formed. Based on these tests, it was discovered that the optimal hardness value of316L stainless Steel material was attained at a deposition period of 90 minutes with a hardness value of 170.10 VHN, and the average thickness of the layer formed was ± 119.02 μm.